Exploration of Bitumen (Natural Asphalt) using a combination of apparent Resistivity method and exploration drilling in Saleh-Abad area, Ilam Province Iran - Salimi, Payam; Motlagh, Asghar Teymoorian; Bisetooni, Kamran Rahimi (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
Bitumen is a hydrocarbon material that accumulates near the earth's surface in the form of asphalt springs or in other forms under the act of hydrostatic pressures of oil reservoirs, it will form bitumen mines after undergoing polymerization process. This mineral (organic) matter is in close relationship to oil reservoirs present in the area, i.e. when oil moves or migrates from one place to another place some part of it will be separated and will remain in the form of streaks, lenses and etc. In this work, the exploration of bitumen resources in Saleh-Abad area, Ilam is carried out using geoelectrical data that were gathered in two-dimensional form, exploration drilling data and also geological data. Today the best method for underground studies and mineral explorations is geophysical studies and drilling exploration wells meanwhile. One of the best data acquisition methods in the Geoelectricity is two-dimensional data acquisition or in other words electrical imaging in two dimensions. Tomography or electrical apparent resistivity tomography is a geophysical technique that investigates underground structures in two or three dimensions. The advantage of ERT method in comparison with other traditional and routine methods is that it investigates the changes of electrical apparent resistivity either laterally (constant spacing traversing or CST) or vertically (vertical electrical sounding, VES) in space. Geophysical data acquisition of the mentioned mine was done using dipole-dipole array in two profiles upon which some points were proposed for exploration drilling. Exploration drilling was done in powder method on the geophysical profiles in six 15-meter bores which proved the high precision of apparent resistivity method for bitumen exploration. Interpretation and modeling of two profiles was carried out using RES2DINV and modeling of drilling Logs was done using LOGPLOT that both had a good conformity with geological data and surface outcrops.